Urinary Cyclophilin A as Marker of Tubular Cell Death and Kidney Injury - Ramio Cabello; Miguel Fontecha-Barriuso; Diego Martin-Sanchez; Ana M. Lopez-Diaz; Susana Carrasco; Ignacio Mahillo; Carmen Gonzalez-Enguita; Maria D. Sanchez-Niño; Alberto Ortiz; Ana B. Sanz (Biomedicines, 2021)
Background: Despite the term acute kidney injury (AKI), clinical biomarkers for AKI reflect function rather than injury and independent markers of injury are needed. Tubular cell death, including necroptotic cell death, is a key feature of AKI. Cyclophilin A (CypA) is an intracellular protein that has been reported to be released during necroptosis. We have now explored CypA as a potential marker for kidney injury in cultured tubular cells and in clinical settings of ischemia-reperfusion injury (IRI), characterized by limitations of current diagnostic criteria for AKI. Methods: CypA was analyzed in cultured human and murine proximal tubular epithelial cells exposed to chemical hypoxia, hypoxia/reoxygenation (H/R) or other cell death (apoptosis, necroptosis, ferroptosis) inducers. Urinary levels of CypA (uCypA) were analyzed in patients after nephron sparing surgery (NSS) in which the contralateral kidney is not disturbed and kidney grafts with initial function. Results: Intracellular CypA remained unchanged while supernatant CypA increased in parallel to cell death induction. uCypA levels were higher in NSS patients with renal artery clamping (that is, with NSS-IRI) than in no clamping (NSS-no IRI), and in kidney transplantation (KT) recipients (KT-IRI) even in the presence of preserved or improving kidney function, while this was not the case for urinary Neutrophil gelatinase-associated lipocalin (NGAL). Furthermore, higher uCypA levels in NSS patients were associated with longer surgery duration and the incidence of AKI increased from 10% when using serum creatinine (sCr) or urinary output criteria to 36% when using high uCypA levels in NNS clamping patients. Conclusions: CypA is released by kidney tubular cells during different forms of cell death, and uCypA increased during IRI-induced clinical kidney injury independently from kidney function parameters. Thus, uCypA is a potential biomarker of kidney injury, which is independent from decreased kidney function.